2020
DOI: 10.1007/s10126-020-10006-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Enterobacter cloacae BAGM01 Producing a Thermostable and Alkaline-Tolerant Rhamnolipid Biosurfactant from the Gulf of Mexico

Abstract: The search for novel biosurfactants (Bs) requires the isolation of microorganisms from different environments. The Gulf of Mexico (GoM) is a geographical area active in the exploration and exploitation of hydrocarbons. Recent metagenomic and microbiologic studies in this area suggested a potential richness for novel Bs microbial producers. In this work, nineteen bacterial consortia from the GoM were isolated at different depths of the water column and marine sediments. Bs production from four bacterial consort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 56 publications
4
1
0
Order By: Relevance
“…Additionally, Rooney et al [ 12 ] reported the production of rhamnolipid biosurfactant from E. hormaechei , achieving a similar surface tension reduction to our findings. Emulsification activities of E. hormaechei on various hydrocarbons and edible oils were observed in our experiment, corroborated by studies by Curiel-Maciel et al [ 30 ]. It is crucial to note that while some Enterobacter species could be pathogenic to humans, not all strains within these species possess virulence factors necessary to cause infection.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, Rooney et al [ 12 ] reported the production of rhamnolipid biosurfactant from E. hormaechei , achieving a similar surface tension reduction to our findings. Emulsification activities of E. hormaechei on various hydrocarbons and edible oils were observed in our experiment, corroborated by studies by Curiel-Maciel et al [ 30 ]. It is crucial to note that while some Enterobacter species could be pathogenic to humans, not all strains within these species possess virulence factors necessary to cause infection.…”
Section: Resultssupporting
confidence: 92%
“…The emulsification index (EI24) of the study isolates ranged from 13.33±0.02% (B18) to 66.29±0.03% (B24). Similarly, Curiel-Maciel et al [ 30 ] observed an emulsification index range of 19.6–63.2% in their study [ 30 ]. The highest emulsification activity was demonstrated by isolate B24 (66.3 %) on kerosene oil, followed by B22 (EI24 63.33 %), B12 (EI24 55.56%) and B20 (EI24 53.33%).…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Notably, the results related to the presence of enzymes involved in oil degradation are consistent with previous works of our own and other groups that investigated the Mexican exclusive economic zone and identified oil-degrading microorganisms derived from 16S amplicon analysis (Fernanda Sánchez-Soto Jiménez et al, 2018;Godoy-Lozano et al, 2018;Hernández-López et al, 2019;Moreno-Ulloa et al, 2019;Raggi et al, 2020;Ramírez et al, 2020); isolated fractions related to petroleum (Moreno-Ulloa et al, 2019); isolated consortia and species capable of degrading petroleum under aerobic and anaerobic conditions (Muriel-Millán et al, 2019;Curiel-Maciel et al, 2021;Rosas-Díaz et al, 2021); and characterized petroleum-degrading enzymes (Rodríguez-Salazar et al, 2020), even in regions with no evidence of anthropogenic perturbation. A recent review illustrated the distribution of bacteria in the water column and sediments of the Mexican exclusive economic zone of the GoM (Rodríguez-Salazar et al, 2021).…”
Section: Identification Of Overrepresented Pathwayssupporting
confidence: 89%
“…On the other hand, the thermostability of the biosurfactant at 10-100ºC (Figure 6B) was evidenced, in agreement with the studies performed by Jamil et al ( 2018) and Curiel-Maciel et al (2021). At 5°C, there was an increase in surface tension (~40 mN/m), suggesting that this surfactant has a Krafft temperature (also known as critical micellar temperature) (Perfumo, et al, 2018) at low values, similar to the biosurfactant lipopeptide produced by Bacillus subtilis N3-1P (Zhu, et al, 2020).…”
Section: Biosurfactant Stabilitysupporting
confidence: 89%